VPA improves ferroptosis in tubular epithelial cells after cisplatin-induced acute kidney injury - Yan Li; Ke Li; Weihao Zhao; Haodong Wang; Xiaodong Xue; Xianghui Chen; Wantao Li; Peihao Xu; Kexin Wang; Pengfei Liu; Xuefei Tian; Rongguo Fu (Frontiers Media S.A., 2023)
Background: As a novel non-apoptotic cell death, ferroptosis has been reported to play a crucial role in acute kidney injury (AKI), especially cisplatin-induced AKI. Valproic acid (VPA), an inhibitor of histone deacetylase (HDAC) 1 and 2, is used as an antiepileptic drug. Consistent with our data, a few studies have demonstrated that VPA protects against kidney injury in several models, but the detailed mechanism remains unclear.Results: In this study, we found that VPA prevents against cisplatin-induced renal injury via regulating glutathione peroxidase 4 (GPX4) and inhibiting ferroptosis. Our results mainly indicated that ferroptosis presented in tubular epithelial cells of AKI humans and cisplatin-induced AKI mice. VPA or ferrostatin-1 (ferroptosis inhibitor, Fer-1) reduced cisplatin-induced AKI functionally and pathologically, which was characterized by reduced serum creatinine, blood urea nitrogen, and tissue damage in mice. Meanwhile, VPA or Fer-1 treatment in both in vivo and in vitro models, decreased cell death, lipid peroxidation, and expression of acyl-CoA synthetase long-chain family member 4 (ACSL4), reversing downregulation of GPX4. In addition, our study in vitro indicated that GPX4 inhibition by siRNA significantly weakened the protective effect of VPA after cisplatin treatment.Conclusion: Ferroptosis plays an essential role in cisplatin-induced AKI and inhibiting ferroptosis through VPA to protect against renal injury is a viable treatment in cisplatin-induced AKI.